PKM MEDIA PEMBELAJARAN BERBASIS CHATGPT DI MTS NEGERI 4 BULUKUMBA - Djafar, Imran; Marsa, Marsa; Bahtiar, Akbar (Yayasan Education and Social Center, 2024)
This internal Community Service, which is funded by the Makassar Dipanegara Foundation, is intended as a form of approach offered to overcome the problems of MTsN 4 Bulukumba teachers. The problems often faced by subject teachers in carrying out their activities within the scope of MTsN 4 Bulukumba are creating materials and teaching materials using methods that are not yet optimal, there is still a lack of understanding about the use of Information Technology and the use of Application Software that supports learning media, especially presentation processing applications. and application software for creating animations. For this reason, we, from the team implementing community service program activities at Dipa University Makassar, are holding Community Service in the form of providing Artificial Intelligence-based Computer and Information Technology (ChatGPT) for school teachers within the scope of MTsN 4 Bulukumba, who have the ability and skill in applying percentage processing software, and processing and creating questions to support the process of creating interactive learning media. The results of this PKM are that participants' knowledge and abilities have increased with user satisfaction assessments through surveys and assessments from PKM participants, the material provided is in accordance with participants' needs and participants feel the benefits of this activity